A Metal‐Free Multicomponent Cascade Reaction for the Regiospecific Synthesis of 1, 5‐Disubstituted 1, 2, 3‐Triazoles1. Issue 50 (13th November 2013) - Cheng, Guolin; Zeng, Xiaobao; Shen, Jinhai; Wang, Xuesong; Cui, Xiuling
<x xml:space="preserve">Abstract</x> About specifics: A method for the regiospecific synthesis of the title compounds through an unprecedented Michael addition/deacylative diazo transfer/cyclization sequence has been established. The simple and practical method can be used for the modification of primary amines including chiral α‐amines. The process involves the formation three covalent bonds and the cleavage of two covalent bonds (see scheme, Ts=4‐toluenesulfonyl).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>